The distribution of field-induced charges in C₆₀ fullerite - Kuprievich, V.A.; Kapitanchuk, O.L.; Shramko, O.V.; Kudritska, Z.G. (Физика низких температур, 2006)
The profile of injected charges in a C₆₀-based field-effect transistor (FET) is considered. A simple
scheme for calculations of the charge distribution between the 2D layers of C₆₀ molecules is
founded on a small magnitude of the interball electron hopping. Analytical solutions of the equations
for the charge distributions are obtained in the limits of thick and thin crystals. The charge
density is shown to drop exponentially with the crystal depth. The calculations predict the relative
part of induced charges involved in the surface layer to be 3/4 and 2/3 in the cases of electron
and hole injection, respectively.